Effect of whitening mouthrinses on enamel toothbrush abrasion - Gomes Torres, Carlos Roctia [UNESP]; Bonicio, Gabrielle Costa [UNESP]; Crastechini, Erica [UNESP]; Mailart, Mariane Cintra [UNESP]; Borges, Alessandra Buhler [UNESP] (Mosher & Linder, Inc, 2018)
Purpose: To evaluate the effect of whitening mouthrinses used before toothbrushing on enamel microhardness and wear. Methods: 80 polished bovine enamel specimens were randomly assigned into four groups according to the mouthrinses tested (n=20): PW: Plax Whitening - 1.5% hydrogen peroxide (HP); LW: Listerine Whitening Pre-Brush Rinse- 2% HP; U: Ultradex - Chlorine dioxide; C: Control - Artificial saliva. The specimens were immersed in the mouthrinses for 1 minute and brushed with 10 strokes, using a dentifrice containing sodium fluoride. After treatments, they were immersed in artificial saliva for 30 minutes. A total of 540 cycles were performed simulating 9 months of use. Enamel surface was assessed with a Knoop microhardness tester and by a contact profilometer before and after treatments to obtain the surface microhardness (KHN) and enamel loss (pm) values. The specimens were immersed in artificial saliva for an additional 30 days and microhardness was measured again. Data were analyzed by ANOVA and Tukey's tests (5%). Results: Significant differences were observed in KHN (P= 0.0001) and wear (P= 0.0001). Results of Tukey's for KHN: U-320.08 +/- 13.86a, PW-323.58 +/- 32.75a, LW-331.66 +/- 24.74a, C-354.24 +/- 16.40b. Wear (um): PW-10.03 +/- 0.94a, LW-9.92 +/- 0.81 a, U-8.88 +/- 1.02b, C-6.56 +/- 0.91c. Groups followed by the same letters do not present significant differences. After 30 days in saliva, there was no significant difference for SMH among the groups.